Abietane diterpenoids and neolignans from the roots of Pinus kesiya - Sa, Nguyen Hoang; Tam, Nguyen Thanh; Hoang Anh, Nguyen Thi; Quan, Tran Duc; Thien, Dao Duc; Sung, Tran Van; Thuy, Trinh Thi (Vietnam Journal of Chemistry, 2017)
The phytochemical investigation of the ethyl acetate extract of Pinus kesiya Royle ex Gordon roots led to the isolation of two abietane diterpenes, 7-oxo-15-hydroxy-dehydroabietic acid (1) and dehydroabietic acid (2) as well as two neolignans, cedrusin (3) and cedrusin-4-O-β-D-glucopyranoside (4). Their structures were determined by combination of spectral analysis and comparison with reported data. Among them, compound 1 was isolated from the genus Pinus for the first time. Keywords. Pinus kesiya, abietane diterpenes, neolignans, dehydroabietic acid, cedrusin.